Bone Marrow–Derived Mesenchymal Stem Cells From Patients With Systemic Lupus Erythematosus Have a Senescence‐Associated Secretory Phenotype Mediated by a Mitochondrial Antiviral Signaling Protein–Interferon‐β Feedback Loop. Issue 8 (11th July 2017) - Gao, Lin; Bird, Anna K.; Meednu, Nida; Dauenhauer, Kristin; Liesveld, Jane; Anolik, Jennifer; Looney, R. John
Abstract : Objective: Bone marrow–derived mesenchymal stem cells (BM‐MSCs) create a special microenvironment for hematopoiesis and immunity and display robust immunomodulatory properties that are impaired in systemic lupus erythematosus (SLE). This study was undertaken to identify the mechanisms of defects in human SLE BM‐MSCs. Methods: Patients fulfilling SLE classification criteria and healthy controls (n = 6 per group) were recruited according to an institutional review board–approved protocol. BM‐MSCs were isolated with low‐density Ficoll‐Hypaque, verified by flow cytometry, and studied using immunocytochemistry, real‐time polymerase chain reaction, Western blotting, comet assay, β‐galactosidase assay, and RNA interference. Results: SLE BM‐MSCs had a senescent phenotype characterized by a reduced proliferation rate, increased production of reactive oxygen species, increased DNA damage and repair, increased expression of p53 and p16, which block the cell cycle, and altered cytokine production (increased proinflammatory cytokine production and decreased immunomodulatory cytokine production). Moreover, SLE BM‐MSCs had a 5‐fold increase in interferon‐β (IFNβ) levels ( P < 0.05 versus healthy controls) and increased IFNβ‐induced messenger RNAs (mRNAs), including mRNA for the intracellular nucleic acid–sensing adaptor protein mitochondrial antiviral signaling protein (MAVS), whose expression was highly correlated with IFNβ levels (r > 0.9, P < 0.01). Since MAVS is known to induce IFNβ production, we hypothesized that there is a positive feedback loop between MAVS and IFNβ. Notably, silencing of MAVS markedly decreased IFNβ, p53, and p16 protein levels and expression of mRNAs for proinflammatory cytokines. Conclusion: This study demonstrates a novel pathway for elevated IFNβ signaling in SLE that is not dependent on stimulation by immune complexes but rather is cell intrinsic and critically mediated by IFNβ and MAVS, implicating new pathways as potential therapeutic targets.